Industrial Development Report 2004 - United Nations Industrial Development Organization (United Nations, 2005)
The Industrial Development Report is intended to build on development policy experience and contribute to a refinement of the international development agenda. The Report pays special attention to current needs and capabilities in the developing countries in general, and the least developed among them in particular. The 2004 edition addresses the challenges faced by Sub-Saharan African countries in furthering their efforts towards poverty reduction and reaching the Millennium Development Goals.